Development of ultrahigh-entropy ceramics with tailored oxidation behavior. Issue 12 (September 2021) - Mellor, William M.; Kaufmann, Kevin; Dippo, Olivia F.; Figueroa, Samuel D.; Schrader, Grant D.; Vecchio, Kenneth S.
Graphical abstract: Highlights: The paper details the first synthesis of bulk ultra-high entropy ceramics with 6 to 9 metal cations, using machine learning as a guiding tools. In addition to reporting single-phaseformation and several mechanical properties for all seven compositions studied, we demonstrate the potential for designer ceramics for oxidative environments. The 7-cation system tested has a uniqueability, when compared to the 5-cation composition tested, to develop a high-entropy transition layer between the oxide and substrate layers. This is found to create a more uniform oxide layer and slow the oxidation rate. Abstract: In the last decade, single-phase high-entropy materials have attracted considerable research interest owing to their unexpected existence and unique combinations of properties. Recent development of 5-cation high-entropy carbides (HECs) has demonstrated alluring properties compared to the rule of mixtures and binary carbides. Proposed here is the development of ultrahigh-entropy carbides (UHECs) containing 6+ principal elements with greater combinatorial possibilities. The use of 6+ multi-cation compositions allows for the design of ceramics with further tunable properties, while likely possessing higher orders of entropic stabilization. There are 133 possible carbide compositions containing 6, 7, 8, or 9 refractory metal cations in equiatomic ratios. Candidate selection for fabrication and material testing was accelerated using a machine learning model that was originally trained to predict the synthesizability of five cation disordered metal carbides. Two compositions from each category of six through eight cations, one containing Cr and one without, plus the one possible nine cation carbide were fabricated and characterized. The potential for these 6+ cation UHECs as improved materials for oxidative environments is demonstrated by comparing the oxidation performance of a 5- and 7-cation system after 10 min at 1973 K in air. The oxidation behavior is correlated with Ellingham diagrams, and it is demonstrated that the 7-cation carbide has the ability to form a transitional stable 5+ cation HEC layer as elements preferentially form oxides, which results in significantly improved oxidation resistance.